Technology-based assessments for 21st century skills : theoretical and practical implications from modern research - Mayrath, Michael C.; Clarke-Midura, Jody; Robinson, David H.; Schraw, Gregory (Emerald Publishing Limited : Information Age Pub., 2011)
Creative problem solving, collaboration, and technology fluency are core skills requisite of any nation's workforce that strives to be competitive in the 21st Century. Teaching these types of skills is an economic imperative, and assessment is a fundamental component of any pedagogical program. Yet, measurement of these skills is complex due to the interacting factors associated with higher order thinking and multifaceted communication. Advances in assessment theory, educational psychology, and technology create an opportunity to innovate new methods of measuring students' 21st Century Skills with validity, reliability, and scalability.In this book, leading scholars from multiple disciplines present their latest research on how to best measure complex knowledge, skills, and abilities using technology-based assessments. All authors discuss theoretical and practical implications from their research and outline their visions for the future of technology-based assessments.
Keywords: Educational tests and measurements -- Data processing.; Educational tests and measurements -- Computer programs.; Education -- Effect of technological innovations on.; Educational innovations.; Education -- Computers & Technology.; Education: examinations and assessment.; Educational equipment and technology, computer-aided learning (CAL); elektronické knihy; electronic books